IMPROVING PRE-WRITING ABILITY IN CHILDREN AGED 4-5 WITH FREE DRAWING USE (Classroom Action Research in Aisyiyah Bustanul Athfal 1 Kindergarten Probolinggo City) - Safitri Dia Pramita, Safitri Dia Pramita (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research was conducted to solve problems that have been faced by educators related to improving writing skills in early childhood 4-5 years at the kindergarten level. This research is expected to provide knowledge related to improving pre-writing skills with the habit of drawing done every day. This study used a qualitative approach with classroom action research methods conducted at TK Aisyiyah Bustanul Athfal 1 Probolonggo in group A with a total of 18 students, consisting of 9 male students and 9 female students. Data collection techniques used are tests, observation and documentation. The result is that the habit of drawing regularly can improve the pre-writing abilities of children aged 4-5 years. Because they are used to holding drawing tools, their fine motor skills continue to be stimulated, so it really helps children to hold writing instruments well. There was a regular increase from pre-cycle to cycle II, when the pre-cycle percentage obtained was 56% then increased by 22% in the first cycle to 78%. Furthermore, in cycle II there was an increase again by 19% to 92%.